The Effect of Easy Perception and Website Quality on Purchase Decisions in Marketplace Tokopedia - Euis Widanengsih (Kusuma Negara Business School, 2020)
This research was conducted by conducting a review on the Tokopedia website, regarding the effect of perceived ease and quality of the website on purchasing decisions both partially and simultaneously, by distributing questionnaires online via email, the population in this study were all users of the Tokopedia site. Probability Sampling is purposive sampling, the criteria of purposive sampling in this study are willing and have time to fill out questionnaires and have transacted with the Tokopedia web. in this study disseminating to 100 respondents via email, but only 85 respondents sent back and completed the questionnaire, the data collected was further processed using SPSS software. The results showed the perception of ease and quality of the website had a significant effect on purchasing decisions both partially and simultaneously. Therefore, Tokopedia management should further enhance the ease of tools in finding and transacting, including by making the system clear and easy to understand, it does not require much effort to interact with the website, it is easy to use and operate. Tokopedia management is also expected to further improve the quality of its website, by reducing time loading, navigation, information, order processing, friendliness of customer service, accuracy of product information and security and privacy in transactions.